Fossil and subfossil primates from the limestone deposits At Taung, Bolt's farm and Witkrans, South Africa - Freedman, Leonard (Bernard Price Institute for Palaeontological Research, 1965)
A very considerable number of Primate specimens was excavated by the University of California African Expedition from the various deposits at Bolt's farm, Taung and Witkrans, South Africa. These specimens are all now housed in the Museum of Paleontology at the University of California, Berkeley, where they were examined by Dr. H. B. S. Cooke in 1957-1958 and then sent to the writer for description. The remaining fauna and the geology of the sites are discussed in an unpublished paper by Cooke. The most important of the new primate specimens are described and classified below. The measurements used are from Freedman (1957); the photographs are oriented on the occlusal plane.
Main article
Keywords: Primates; limestone deposits; Bolt's farm; Taung; South Africa